Design and Development of a Multi-Wavelength Brillouin/Erbium Long-Band Fabry Perot Fiber Laser - Haddud, Tarak Ali (2006)
Multi-wavelength fiber lasers operating in the long-wavelength band (L-band) wavelength region are needed as laser source for applications such as wavelengthdivision- multiplexed (WDM) communication systems, fiber sensors, spectroscopy and optical fiber gyroscopes. Multi-wavelength fiber lasers are emerging as attractive alternative technologies for wavelength-selectable WDM. They are used as source for direct compatibility with the fiber-optic transmission medium, excellent amplifying properties of rare-earth doped fibers, Brillouin gain, rapidly continuing progress in novel fiber gain media, maturity and robustness of the laser diode pumps used and availability of fiber-based components The multi-wavelength laser applications of interest to this work have distinct performance requirement. This requirement is the need for wide tunability (the ability to tune the lasing emission through a wide range of wavelengths). In this thesis, the design and development of a multi channel continuous wave Brillouid Erbium L-band fiber laser (BEFL), with novel loop mirror configuration, has been studied experimentally. The design parameters of multi-wavelength fiber laser (launched pump powers, single mode optical fiber lengths and Brillouin wavelengths), the multi wavelength Brillouiderbium linear fiber laser configuration with bi-directional pumping is demonstrated. Throughout this work different lengths of single mode optical fiber with various launched pump powers and Brillouin wavelengths have been examined to extract the optimum output performance of a BEFL. The performance of the BEFL is presented in terms of threshold pump power, output peak power, tuning range and the number of Stokes. This development fiber loop configuration exhibits considerably high performance. Twenty-four of Stokes with 10 nm tuning range and efficient output powers were obtained.